Charlie is broken! - Child, Lauren; Hurst, Bridget; Tiger Aspect Productions (New York : Grosset & Dunlap, 2009)
Lola tries to find a way to lift Charlie's spirits when he breaks his arm, cutting short their plans to put on a circus show.
"Text based on the script written by Bridget Hurst, illustrations from the TV animation produced by Tiger Aspect"--T.p. verso.
2.1
K-3.
K-3
Keywords: Charlie (Fictitious character : Child) -- Juvenile fiction; Lola (Fictitious character : Child) -- Juvenile fiction; Wounds and injuries -- Juvenile fiction; Charlie (Fictitious character : Child) -- Fiction; Lola (Fictitious character : Child) -- Fiction; Wounds and injuries -- Fiction; Charlie (Fictional character : Child) -- Fiction; Lola (Fictional character : Child) -- Fiction; Radio and television novels; Wounds and injuries -- Fiction; Picture books for children; Radio and television novels